(2/3)x-5=x/6

Simple and best practice solution for (2/3)x-5=x/6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2/3)x-5=x/6 equation:


x in (-oo:+oo)

(2/3)*x-5 = x/6 // - x/6

(2/3)*x-(x/6)-5 = 0

1/2*x-5 = 0 // + 5

1/2*x = 5 // : 1/2

x = 5/1/2

x = 10

x = 10

See similar equations:

| (6y+7)-(6+5y)=11 | | -0.10(47)+0.80x=0.05(x-4) | | (-7c*-4)+8x=12+14 | | 3(1-9x)+4x= | | 3/7-2=20 | | x/3-x=-12-2x/9 | | 8x+(9x-5)= | | 4x-6-3x=16-20 | | 38=-x-6x-4 | | ((-3)-(-2)(9))= | | 8-2(4-x)=2x+3x | | 24=-2x-x-3 | | 3x+2x=200 | | 2=.3x-.5x-7 | | (y/9)=(8/5) | | G(x)=2x^2-8x+4 | | 7x-7=2x | | 105=4x+4x+9 | | 8v+5(4v-10)= | | A=(95)(61) | | 2.4p-16=3.4p-11 | | y/9=8/5 | | 9x-2x+3=x-8+11 | | 2x-3+4=0 | | 2*5+1+4c-3=40 | | (2a+3b)(3a+2b)= | | 5*6-1+3b+4=48 | | 9x/5=18 | | 2a+6+5a-4=44 | | 2a+6b-5a-b+1= | | 9x+13y=12000 | | x/6-5/8=7/8 |

Equations solver categories